Partisipasi Politik Generasi Muda di Era Digital: Antara Kesadaran Kritis dan Aktivisme Daring - Katili, Andi Yusuf; Katili, Andi Abee Zoelthan; Pariono, Agus (CV. Dalle’ Deceng Abeeayla, 2025)
This study aims to analyze how young people engage in political activities through digital media and to what extent such activities reflect critical political consciousness and meaningful online activism. The research employs a descriptive-qualitative approach using literature analysis and secondary data from empirical studies on digital political participation conducted between 2015 and 2025. The development of digital technology has fundamentally transformed the forms and patterns of youth political participation. The findings indicate that social media has become a new arena for youth political expression and mobilization, with platforms such as Instagram, TikTok, and X (Twitter) playing a significant role in the dissemination of political information and social campaigns. However, most of these activities remain symbolic and are not accompanied by a substantive understanding of political issues. The phenomenon of slacktivism and the lack of political literacy remain major obstacles to achieving meaningful political engagement. This study concludes that digital democracy in Indonesia requires the strengthening of political literacy and critical awareness so that young people can move beyond being mere social media users to becoming reflective and constructive agents of social change.